Nonlinear Control of a Buck Converter Feeding a Constant Power Load - Solsona, Jorge Alberto (2014)
In this paper a nonlinear control strategy for controlling a dc/dc Buck converter feeding a constant power load is proposed. A feedback controller is combined with a feedforward strategy. A nonlinear reduced order observer is used for estimating the value of the power load and its time derivative. These estimated values are fed forward to the nonlinear feedback controller whose design is based on feedback linearization method. The proposed controller is tested via simulations and also, experimental results are presented.